Effectiveness of Vortioxetine in Patients With Major Depressive Disorder in Real-World Clinical Practice: Results of the RELIEVE Study - Mattingly, Gregory W.; Ren, Hongye; Christensen, Michael Cronquist; Katzman, Martin A.; Polosan, Mircea; Simonsen, Kenneth; Hammer-Helmich, Lene (Frontiers in Psychiatry, 2022)
Background: Randomized controlled clinical trials have shown vortioxetine to be efficacious and well tolerated for the treatment of major depressive disorder (MDD). The Real-Life Effectiveness of Vortioxetine in Depression (RELIEVE) study was undertaken to demonstrate the effectiveness and safety of vortioxetine for the treatment of MDD in routine clinical practice. Methods: RELIEVE was a 24-week, observational, prospective cohort study in outpatients with MDD initiating treatment with vortioxetine at their physician’s discretion in routine care settings in Canada, France, Italy, and the USA (NCT03555136). The primary study outcome was patient functioning assessed by the Sheehan Disability Scale (SDS). Secondary outcomes included depression severity (9-item Patient Health Questionnaire [PHQ-9]), cognitive symptoms (5-item Perceived Deficits Questionnaire-Depression [PDQ-D-5]), and cognitive performance (Digit Symbol Substitution Test [DSST]). Mixed models of repeated measures were used to assess change from baseline at week 24, adjusted for relevant confounders. Results: A total of 737 patients were eligible for inclusion in the full analysis set. Most patients (73.7%) reported at least one comorbid medical condition, 56.0% had comorbid anxiety and 24.4% had comorbid generalized anxiety disorder. Improvement in least-squares (LS) mean SDS score from baseline to week 24 was 8.7 points. LS mean PHQ-9, PDQ-D-5 and DSST scores improved by 7.4, 4.6, and 6.2 points, respectively. Adverse events were observed in 21.2% of patients (most commonly, nausea [8.2% of patients]). Conclusions: These results demonstrate the effectiveness and tolerability of vortioxetine for the treatment of MDD in a large and heterogeneous patient population representative of that encountered in routine clinical practice.